Country Partnership Framework for the Socialist Republic of Vietnam for the Period FY18-FY22 - World Bank (World Bank, Washington, DC, 2017)
Thirty years after the launch of the economic reforms known as Doi Moi, Vietnam is considered a development success story—marked by remarkable poverty reduction and economic growth. Notwithstanding notable achievements, development challenges persist. The last World Bank Group (WBG) country strategy for Vietnam, the FY12–16 Country Partnership Strategy (CPS), was presented to the WBG Board of Directors on December 15, 2011.The Vietnam Country Partnership Framework (CPF) covers the period FY18–22. It has been prepared based on analysis and conclusions in Vietnam 2035: Toward Prosperity, Creativity, Equity, and Democracy (Vietnam 2035)1 and in the 2016 Vietnam Systematic CountryDiagnostic (SCD), and informed by the CPS Completion and Learning Review (CLR) and the 2016 Client Survey. The CPF is fully aligned with the Government of Vietnam’s (GoV) 2010–20 Socio-Economic Development Strategy (SEDS) and the recent 2016–20 Socio-Economic Development Plan (SEDP). The CPF responds to priorities for support expressed by the government and builds on the WBG’s comparative advantage.The CPF is prepared at a critical juncture in Vietnam’s development and at a time of transition. FY18 represents a new period in GoV–WBG relations as Vietnam graduates from the International Development Association (IDA) at end-FY17. Moreover, success raises expectations—Vietnam has high ambitions for further development and growth, aspiring to modernity, industrialization, and a better quality of life.The CPS has three pillars: (i) strengthen Vietnam’s competitiveness in the regional and global economy; (ii) increase sustainability of the country’s development; and (iii) broaden access to economic and social opportunity, supported by three cross-cutting themes: (a) strengthen governance, (b) promote gender equality, and (c) improve resilience related to external economic and climatic shocks.